A The Dilemmatization of Women's Roles in a Time of Pandemic (Study on Female Teachers at West Sukolilo Elementary School, Labang Bangkalan Madura) - Eni Syafitri; Fitria Dayanti; Fenda Nuradifa C. P.; Diyah Utami (Metafora: Education, Social Sciences and Humanities Journal, 2022)
AbstractThe pandemic creates various pressures and problems in all aspects. Education is the most interesting issue to be described and analyzed. Changes in learning locations can reduce the intensity of student enthusiasm, network barriers, and the slow adaptation process. It can also cause the quality of education to decline, especially at the elementary school level. Students are required to understand learning and are expected to be able to understand all methods that lack support. In addition to teachers as educators, parents also have the same burden as teachers, namely guiding children when learning is carried out. The role of women during the pandemic is experiencing a dilemma, including teachers. Female teachers in addition to having an obligation to their status as a teacher also have a domestic burden that must be done at home. Female teachers have multiple roles and the workload increases while at home. The roles of wives, mothers, and educators are not easy to harmonize. This problem can interfere learning process because it results in lessoptimal implementation as evidenced by students who have difficulty understanding. The purpose of this study was to analyze the role of teachers as educators and domestic duties and to guide their children for online learning. The theory used is liberal feminism which focuses on women and the world of work. This theory is considered very suitable because the theme in this study discusses the position of women and their roles. The method used is descriptive qualitative. So, the results in this study reveal female teachers have more than two roles (i.e. dualism). Apart from being an educator, she also doubles as a mother and wife who takes care of homework during working hours. It has a major impact on her professionalism as an educator.Keywords: Dual role, female teacher, Pandemic, Feminism.